Circulating pictures: photography and exhibition in the Portuguese Pavilion at Expo 58. Issue 4 (2nd October 2019) - Martins, Susana S.
Abstract : This article examines the interplay between photography and universal exhibitions, two modern phenomena which, in different ways, have allowed for the world to be seen and reconfigured in unprecedented ways. It considers world exhibitions not just as sites of movement but also as systems that crucially rely on the circulation of photographic images. Focusing on a specific, and so far unexamined, case study – the Pavilion of Portugal at Brussels Expo 58 –, this work combines historical reconstruction and critical analysis to demonstrate how photography and exhibitions are mutually affected and transformed by the contexts in which they are made available. Particular attention is paid to the way humanism has been photographically integrated into the national discourse, and to the role invisibility plays in both exhibition and propaganda processes. Moreover, it is argued that despite the profusion and impressive scale of the photomurals in the pavilion, photography occupied a significantly subordinate role in the broad exhibition programme. Investigating how photographs functioned at different levels and purposes, before, during and after the exhibition, this article excavates several discourses, networks, and photo-textual interactions, to evidence how the history of photography and the history of exhibitions are often inseparable from one another.